Itineraries for the Training of Educational Researchers in Mexico - Luis Alan Acuña Gamboa; Leticia Pons Bonals (Universidad Autónoma de Madrid, 2019)
This research was built upon the recognition of the what, the how/where, and the for what of the fie, with the purpose of exploring the itineraries and meanings that the Training of Educational Researchers (fie, for its acronym in Spanish) assumes in Mexico, in a scenario marked by the marketing of education. The research, exploratory-descriptive, contemplated a quantitative and qualitative methodology. First, at the quantitative level, which started with the recognition and characterization of the educational offer (292 doctorates of which 41 were selected); secondly, at the qualitative level, that interprets the different meanings that the fie assumes in these educational programs. The debate over the results goes beyond the mere description of the perversions on which diverse authors focus. Such authors tend to center their attention on the facilitation of the processes for obtaining academic degrees, the confrontation between public and private education, and the submission of education to the laws of a competitive market. The authors of this paper, rather, aim at transcending the exploratory level to deepen into the analysis of the transformations experienced by the fie, such as the virtualization and the presence of different interests for the training which necessarily changes the traditional meanings of this training while opening new paths towards their understanding.